The effect of cannabinoids on the stretch reflex in multiple sclerosis spasticity. (July 2016) - Marinelli, Lucio; Mori, Laura; Canneva, Stefania; Colombano, Federica; Currà, Antonio; Fattapposta, Francesco; Bandini, Fabio; Capello, Elisabetta; Abbruzzese, Giovanni; Trompetto, Carlo
Abstract : The aim of this observational study was to assess the efficacy of a tetrahydrocannabinol–cannabidiol (THC : CBD) oromucosal spray on spasticity using the stretch reflex in patients with multiple sclerosis (MS). Numeric rating scale (NRS) for spasticity, modified Ashworth scale (MAS), and the stretch reflex were assessed before and during treatment in 57 MS patients with spasticity eligible for THC : CBD treatment. A significant reduction in stretch reflex amplitude as well as significant reductions of NRS and MAS scores were observed. There was a low concordance between the three measures (stretch reflex, NRS, and MAS), likely related to the different aspects of muscle hypertonia assessed. Stretch reflex responders were taking a significantly higher number of puffs, whereas no differences were found in the responders by the other scales, suggesting that a higher dosage would add benefit if tolerated. The present study confirms the efficacy of cannabinoids in reducing spasticity in patients with MS, suggesting a higher sensitivity and specificity of the stretch reflex compared with other measures. As an objective and quantitative measure of spasticity, the stretch reflex is particularly useful to assess the effects of cannabinoids on spinal excitability and may play a role in future pharmacological studies.